Effectiveness of Contextualized Marungko Approach-Based Supplementary Reading Material - Repaso, Jophel C.; Macalisang, Denmark S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Acquiring solid reading skills is significant in education as it is the cornerstone for academic success and lifelong learning. This sequential explanatory mixed-methods study investigates the effectiveness of a contextualized Marungko approach-based supplementary reading material in improving the reading performance of Grade 1 pupils. In the pre-experimental phase the Early Grade Reading Assessment (EGRA) tool was utilized to measure the reading skills of the twenty four (24) Grade 1 pupils in terms of identifying letter sounds, identifying initial sounds, reading familiar words, reading invented words, and reading oral passages before and after the implementation of the contextualized Marungko approach-based supplementary reading material. Findings revealed a significant improvement in the early reading skills of Grade 1 pupils after using the supplementary reading material. This indicated that the reading material effectively enhanced the Grade 1 pupils’ reading performance. The responses of the five (5) participants in the qualitative phase, which were examined following Braun and Clark (2013) analysis, yielded two (2) themes. It is recommended that educational institutions and policymakers should consider incorporating the Marungko Approach into their reading instruction programs to enhance alphabet knowledge, phonemic awareness, word recognition, decoding, and oral reading fluency.